Efficacy of an Individually Tailored, Internet-Mediated Physical Activity Intervention in Older Adults: A Randomized Controlled Trial. (July 2019) - Rowley, Taylor W.; Lenz, Elizabeth K.; Swartz, Ann M.; Miller, Nora E.; Maeda, Hotaka; Strath, Scott J.
Objective: This study determined the effectiveness of an individually tailored, Internet-mediated physical activity (PA) intervention for increasing walking behavior in inactive older adults.Method: This 12-week randomly controlled intervention divided participants ( N = 170) into three groups: control (CON, n = 51), pedometer only (PED, n = 62), and an individually tailored, Internet-mediated pedometer (TI-PED, n = 57) group. The PED group was instructed to increase weekly step count by 10% until 10, 000 steps per day was achieved. The TI-PED group was given the same goal and received tailored feedback via an online platform. Changes in average step count pre-to-post were assessed.Results: Total retention rate at postintervention was 75.3%. PED ( p < .001) and TI-PED ( p < .001) increased step count pre-to-post, which was higher than the CON group at 12 weeks (PED, p < .001; TI-PED, p < .001). The TI-PED group had a higher step count at 12 weeks than the PED group ( p < .001).Discussion: Individually tailored, Internet-mediated PA interventions are an effective way to significantly increase PA in older adults.